Lymph node involvement is associated with overall survival for elderly patients with non-metastatic gallbladder adenocarcinoma - Huang, Jianhao; Qiu, Yanyu; Bai, Xuesong; He, Xiaodong (Frontiers in Surgery, 2024)
Lymph node involvement is recognized as a prognostic factor of the patients with gallbladder cancer. However, the N stage varied from different editions of AJCC TNM Classification. Our objective was to investigate the impact of lymph node involvement on overall survival in elderly patients with non-metastatic gallbladder adenocarcinoma.Patients older than age 65 years with non-metastatic gallbladder adenocarcinoma were identified from the SEER data. We used Cox proportional hazard regression analysis to select the independent risk factor. A nomogram was built to identify the 1-, 3-, and 5years prognostic impact. Univariate and multivariate models were used to examine the correlation of OS with the number of metastatic nodes.A total of 1654 patients (706 with and 948 without nodal involvement) were included.Cox proportional hazard regression analyses found that age, gender, tumor size, lymph node involvement and surgical options were risk factors for the prognosis and were integrated into the nomogram. After adjustment, OS was compromised for patients who receive surgery with nodal involvement (HR, 2.238; P <0.01). After adjustment, the presence of more than two metastatic lymph nodes was associated with decreased OS (HR, 3.305; P <0.01).Our results suggest that lymph node involvement are associated with compromised survival in elderly patients. A nomogram was developed to predict the prognosis of gallbladder cancer. A change point of more than two metastatic lymph nodes seems to carry prognostic significance, calling for closer monitor to elderly gallbladder cancer patients with increased number of lymph node involvement.